PERAN DIVISI TALENT DALAM WISUDA PURNABAKTI TELKOM INDONESIA 2023 OLEH PT METRA DIGITAL MEDIA - Fidelia, Evelyn; Syah, Firman (Bisnis Event, 2025)
The phenomenon of "retirement graduation" has become significant as a form of recognition and celebration of the achievements of individuals who have fully dedicated themselves to the mission and vision of the pendidikan.PT institution Telkom Indonesia routinely holds a Retirement Graduation Ceremony as a form of appreciation for the dedication and contribution that has been given by the participants to Telkom Indonesia. The purpose of this report is to present detailed information about the role of the Talent Division in the management of the performers, involving aspects of preparation, implementation, and closing of the event. The research method used is to use a qualitative method with a descriptive approach. The result of this research is that there are stages carried out by the Talent Division in the 2023 Telkom Retirement Graduation, namely the preparation stage, including the process of contacting talents to rehearsals. The implementation stage includes a mechanism process that is implemented in accordance with the Talent Division planning. The last is the obstacle faced by the talent division in the implementation of the 2023 Telkom Indonesia Retirement Graduation event. Keyword: Role, Talent Division, Retirement Graduation